2020
DOI: 10.48550/arxiv.2008.00582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

audioLIME: Listenable Explanations Using Source Separation

Abstract: Deep neural networks (DNNs) are successfully applied in a wide variety of music information retrieval (MIR) tasks but their predictions are usually not interpretable. We propose audioLIME, a method based on Local Interpretable Model-agnostic Explanations (LIME), extended by a musical definition of locality. The perturbations used in LIME are created by switching on/off components extracted by source separation which makes our explanations listenable. We validate audi-oLIME on two different music tagging system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The input is perturbed by switching "on/off" the individual segments. AudioLIME (Haunschmid et al, 2020;Chowdhury et al, 2021) proposes to separate input using predefined sources to create the simplified representation. AudioLIME arguably generates more meaningful interpretations than SLIME as it relies on audio objects readily listenable for end-user.…”
Section: Interpretability Methods For Audiomentioning
confidence: 99%
See 1 more Smart Citation
“…The input is perturbed by switching "on/off" the individual segments. AudioLIME (Haunschmid et al, 2020;Chowdhury et al, 2021) proposes to separate input using predefined sources to create the simplified representation. AudioLIME arguably generates more meaningful interpretations than SLIME as it relies on audio objects readily listenable for end-user.…”
Section: Interpretability Methods For Audiomentioning
confidence: 99%
“…Particularly, APNet (Zinemanas et al, 2021) is not designed for post-hoc interpretations. AudioLIME (Haunschmid et al, 2020) is not applicable on our tasks as it requires known predefined audio sources. Moreover, SLIME (Mishra et al, 2020) and AudioLIME still rely on LIME (Ribeiro et al, 2016) for interpretations.…”
Section: Evaluation Metrics and Baselinesmentioning
confidence: 99%
“…The input is perturbed by switching "on/off" the individual segments. AudioLIME [32], [33] proposed to separate the input using predefined sources to create the simplified representation. AudioLIME arguably generates more meaningful interpretations than SLIME as it relies on audio objects readily listenable for end-users.…”
Section: B Audio Interpretabilitymentioning
confidence: 99%
“…In Raj et al (2019), probing on x-vectors trained solely to predict the speaker label, revealed they also contain incidental information about the transcription, channel, or meta-information about the utterance. Probing the Music Information Retrieval (MIR) prediction through Local Interpretable Model-Agnostic Explanations (LIME) by using Audi-oLIME (Haunschmid et al, 2020) helped interpret MIR for the first time. They demonstrated that the proposed AudioLIME produces listenable explanations that creates trustworthy predictions for music tagging systems.…”
Section: Audio Probingmentioning
confidence: 99%